Inhibitory effect of traditional Korean medicine on the recurrent endometriosis after laparoscopic excision: a case report - Hae-Won Kim; Jeong-Eun Yoo (Integrative Medicine Research)
Endometriosis is a common benign gynecologic tumor, and it can destroy a patient's life. Surgery and hormone therapy are established therapies for endometriosis. However, there are many cases of recurrent endometriosis after conventional therapies. This report presents a case of a patient who has repetitive recurrence of endometriosis after laparoscopic excision and hormone therapy. A 32-years-old female patient first had laparoscopic surgery to remove endometriosis in 2011. The disease recurred two more times after the first excision. Hormone therapy by dienogest and two more laparoscopic surgeries were done in 2012 and 2014. With acupuncture, moxibustion, fumigation therapy, and herbal medicine therapy, endometriosis didn’t recur during treatment and observation period of 34 months. Menstrual pain numeric rating scales (NRS) decreased from 2 to none. Shortened menstrual cycle (24 days) after second surgery became longer (26.63 ± 2.28 days) after traditional Korean medicine therapy. This case presents the therapeutic potential of TKM for inhibitory effect on the recurrent endometriosis after laparoscopic excision and hormone therapy. Keywords: Boheotang, Dienogest, Endometriosis, Laparoscopic surgery, traditional Korean medicine